(untitled) (Journal of Information Technologies in Education (ITE), 2013)
The issues of introduction of electronic textbooks are examined in the article. A concept of digitizing levels of content is introduced. A concept of semantic textbook is introduced. A role of electronic textbooks in granting access to educational content is represented. The issues of electronic textbook formats are examined. A background and problems of wide introduction and spreading of electronic textbooks are considered.